(untitled) (Research, Society and Development, 2022)
Kidney transplantation is the most frequent type of organ transplantation in Brazil, has a complex process, involving ethical, immunological aspects added to specific conditions of the donor and the recipient, and that can cause postoperative problems, including hypertension. The SAH developed after renal transplantation correlates with negative cardiovascular and renal outcomes, leading to impaired renal function, decreased graft survival and increased mortality from these causes. The proposal consists of an integrative review of the literature on the genesis of systemic arterial hypertension in patients after renal transplantation, composed of original articles, published from 2012 to 2022, in peer-reviewed journals, languages, and that allow full access to the content. It was seen that the genesis of hypertension in renal transplant patients can be related to factors such as the production of vasopressor substances that support RAAS, use of immunosuppressants such as glucocorticoids and INC, as well as stenosis or thrombosis of the renal graft artery, Arteriovenous fistula and the presence of proteinuria after the transplantation procedure, as well as genetic predisposition as a stimulating factor, especially genetic mutations such as APOL1 and CAV-1, whether from the donor or the recipient. It was concluded that systemic arterial hypertension in renal transplants has multifactorial genesis and can systematically impair the normal physiological function of the organ, as well as the loss of the graft and decreased life expectancy of these patients.